2021
DOI: 10.3390/antiox10101635
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Production by the Red Tide-Producing Chattonella marina Complex (Raphidophyceae) Correlates with Toxicity to Aquacultured Fishes

Abstract: The marine raphidophyte Chattonella marina complex forms red tides, causing heavy mortalities of aquacultured fishes in temperate coastal waters worldwide. The mechanism for Chattonella fish mortality remains unresolved. Although several toxic chemicals have been proposed as responsible for fish mortality, the cause is still unclear. In this study, we performed toxicity bioassays with red sea bream and yellowtail. We also measured biological parameters potentially related to ichthyotoxicity, such as cell size,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…However, production of PST in response to the allelopathic effect is unknown. Chattonella marina produces and releases polyunsaturated fatty acids and reactive oxygen species into the marine environment [21][22][23][24], whereas G. impudicum produces mucilage formed by exopolysaccharides [25,26]. During the early exponential phase, G. impudicum can produce superoxide radicals in similar concentrations to those of C. marina var.…”
Section: Introductionmentioning
confidence: 99%
“…However, production of PST in response to the allelopathic effect is unknown. Chattonella marina produces and releases polyunsaturated fatty acids and reactive oxygen species into the marine environment [21][22][23][24], whereas G. impudicum produces mucilage formed by exopolysaccharides [25,26]. During the early exponential phase, G. impudicum can produce superoxide radicals in similar concentrations to those of C. marina var.…”
Section: Introductionmentioning
confidence: 99%
“…Despite extensive studies [ 86 , 88 , 93 , 100 , 159 , 160 , 166 , 171 , 208 , 209 , 210 , 211 , 212 ], the exact mechanism through which Chattonella cause fish death is still poorly understood. Recently, Shikata et al [ 213 ] examined the ichthyotoxicity of eight strains of Chattonella with different backgrounds against different fish species (red sea bream and yellowtail) and found that the generation level of superoxide was most well-correlated with fish-killing activity among several factors examined, which supports the notion that ROS are mainly involved in the Chattonella -related fish mortality.…”
Section: Marine Microalgae Species With Ros-producing Activitiesmentioning
confidence: 84%
“…All strains were isolated from Japanese coastal areas. In cell shape, the length:width ratio of Chattonella antiqua-like cells are larger than Chattonella marina-like cells (Shikata et al, 2021).…”
Section: Monitoring Dvm With a Digital Camera Systemmentioning
confidence: 86%
“…Compared to 4KGY (early log phase), 3KGY has higher surface accumulation ratios during the dark periods and accumulates at the bottom during the light periods in the same experimental setup, indicating that DVM in 3KGY has more entrainability. Although Chattonella shows variations in cell shape and toxicity among strains ( Demura et al, 2009 ; Shikata et al, 2021 ), the relationship between their phenotypes ( Table 1 ) and DVM pattern remains obscure. Our findings indicate that the strain composition of a Chattonella population may influence the vertical cell distribution at each time point in the field, although it is unclear what produced the interstrain differences in the DVM pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation